Investigation of the Relationship Between Subjective Symptoms of Visual Fatigue and Visual Functions - Zheng, Fuhao; Hou, Fang; Chen, Ruru; Mei, Jianhui; Huang, Pingping; Chen, Bingzhen; Wang, Yuwen (Frontiers in Neuroscience, 2021)
Purpose: To investigate whether the severity of symptoms for visual fatigue might be associated with clinical visual measures and basic visual functions, such as accommodation, vergence, and contrast sensitivity. Methods: In this study, 104 students were recruited (25 males, 79 females, Age 23.4 ± 2.5) for this study. Those with high myopia, strabismus, anisometropia, eye disease or history of ophthalmological surgery were excluded. The included subjects completed a questionnaire that assesses the severity of visual fatigue. Then, binocular accommodative facility, vergence facility and contrast sensitivity using a quick contrast sensitivity function approach were measured in a random sequence. Next, the correlations between each symptom of visual fatigue in the questionnaire and accommodative facility, vergence facility and contrast sensitivity were examined. Results: Factor analysis indicated that visual fatigue, as captured by the scores of a subset of the questionnaire items, could be strongly related to binocular accommodative facility and binocular contrast sensitivity, but not to vergence facility. We also found that binocular accommodative facility and contrast sensitivity at high spatial frequencies are related. Conclusion: Our findings suggest that visual fatigue is related to the ability of human observers to encode visual details through their binocular vision.